The Effect of Lifestyle, FoMO, and Self Control On Personal Financial Planning - Septyaningtyas, Dinar Rika; Djunaedi; Laely, Nur (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of the study was to examine the effect of lifestyle, FoMO, and Self-Control on Personal Financial Planning. Design/Methode/Approach: This research is a type of explanatory research using a quantitative approach. The study population is Kediri City Residents. Purposive sampling techniques were used in this study so 96 respondents were used as research samples. The data analysis method used the multiple linear regression test using SPSS Research Finding: The results showed that lifestyle and Self-control partially had a significant positive effect on Personal Financial Planning, while FoMO had an effect but not significant on Personal Financial Planning in Kediri City Residents. Research limitation: The variables of this study are only limited to lifestyle, FoMO, and Self-Control.